Recent Development of Spray Reagents for the Detection of Amino Acids on Thin Layer Chromatography Plates: An Overview - Basu, Sarmistha; C. Dey, Milan; Kundu, Somenath; Sinhababu, Amalendu (Mini-Reviews in Organic Chemistry, 2016)
Identification of amino acids helps in evaluating the structure of protein/polypeptide since the amino acids are the building blocks of the later. Many specific and non-specific reagents have been used to detect amino acids on thin-layer chromatographic (TLC) plates, among them ninhydrin is most widely used for its remarkable high sensitivity. It produces same purple/violet color with all amino acids, except proline and hydroxyproline which produce yellow color. During the last three decades, a good number of new reagents have been introduced to overcome the color problem of ninhydrin with different amino acids as well as to enhance the degree of sensitivity for such detection. In this study some recent developments of such spray reagents for the detection of amino acids on TLC plates have been thoroughly reviewed.
Keywords: thin-layer chromatography